Pengaruh waktu anodizing dan jarak anoda-katoda terhadap nilai laju korosi Aluminium 6061-T6 - Eko Budiyanto; Yususf Rizal fauzi (Jurnal INOVATOR, 2019)
This research was conducted to identify how influential the duration and anode-cathode distance to the corrotion rate produced in the anodizing process so that it can be used to consider the effectiveness of an anodizing process. This research has been used regular anodizing techniques commonly used for decorative purposes. The method has been used is to vary the anodizing duration (2, 4, and 6 minutes) and anode-cathode distance ( 18, 20, and 22 cm) and apllied the weight loss method to calculated corrotion rate value. The result is that the highest corrotion rate is obtained at 4 minutes anodizing duration and 18 cm anode-cathode distance by 663,7 mm/year, while the lowest corrotion rate is found in 3 exsperiments, at 2 minutes anodizing duration for 20 cm and 22 cm anode-cathode distance, and at 4 minutes anodizing duration for 22 cm anode-cathode distance by 442,5 mm/year.